Chest compression rates of 60/min versus 90/min during neonatal cardiopulmonary resuscitation: a randomized controlled animal trial - Bruckner, Marlies; O'Reilly, Megan; Lee, Tze-Fun; Cheung, Po-Yin; Schmölzer, Georg M. (Frontiers in Pediatrics, 2023)
Take-home message: Using a slower chest compression rate of 60/min compared to the currently recommended rate of 90/min results in similar hemodynamic and respiratory outcomes during neonatal cardiopulmonary resuscitation. Although the ideal compression rate for optimal oxygen delivery and organ perfusion warrants further investigation, healthcare providers may focus on delivering adequate compression depth and technique rather than achieving correct rate.Reducing chest compression rate to 60/min has no adverse affect during neonatal cardiopulmonary resuscitation.